Acurácia dos indicadores clínicos do diagnóstico de enfermagem motilidade gastrintestinal disfuncional em crianças - Vieira, Larissa Gabrielle Dias (2016)
The study aimed to analyze the accuracy of measures of clinical indicators of diagnosis of dysfunctional gastrointestinal motility nursing children in neonatal care units. The nursing diagnosis that belongs to the taxonomy of NANDA-I and is defined as "increased peristaltic activity, decreased, ineffective or absent from the gastrointestinal system." This diagnosis can be evidenced by clinical indicators increased gastric residue, absence of flatus, diarrhea, difficulty in eliminating feces, abdominal distension, abdominal pain, accelerated gastric emptying, hard stools, changes in bowel sounds (absent, present, hypoactive, hyperactive), nausea, regurgitation, gastric residual color of bile, vomiting and abdominal cramps. It is a study of diagnostic accuracy, cross-sectional, exploratory and descriptive design. The study was conducted in two hospitals characterized by care, teaching and research. The study sample consisted of 228 children in two hospitals. They were adopted as inclusion criteria: children with a minimum stay of 24 hours, gestational age between 25 and 42 weeks, proven by the scale of New Ballard or evaluation technique of somatic Capurro. To collect the data, we used an instrument that guided the realization of abdominal physical examination and consultation with the medical records of children. Data were organized in Excel (2007) for further analysis with the support of R version 2.12.1 software. the descriptive analysis through the calculation of absolute frequencies, percentages, central tendency and dispersion measurements was performed. They were also calculated sensitivity of accuracy and specificity of each clinical indicator, based on Latent Class Analysis method. This study followed the ethical principles for research established by Resolution No. 466 of the National Council was approved by the Research Ethics Committee of the Federal University of Ceará as Opinion No. 1,311,771. The study showed that the dysfunctional gastrointestinal motility nursing diagnosis was prevalent in 52.3% of the sample. The clinical indicator Residual Gastric was identified in 52.6% of the sample, followed by Intestinal Sons changes with 46.5% Regurgitation with the percentage of 39.5% and abdominal distension with 39.5%. gastric residual increase showed high levels of sensitivity and specificity, especially as most important clinical indicator for the inference dysfunctional gastrointestinal motility. Changes in bowel sounds, regurgitation, gastric Residue color of bile, flatus and faeces Absence hardened appeared as specific indicators. It is believed that the knowledge acquired by nurses through this research can contribute to the diagnosis of dysfunctional gastrointestinal motility nursing is identified in children hospitalized in neonatal units. It is worth noting that the accuracy of measures of clinical indicators have relevance to more accurate inference of said nursing diagnosis.